Study of Assistance Development of Thematic Learning Material by Integrating New Literacy and Disaster Literacy on Science Teachers - Asrizal Asrizal; Wahyuni Satria Dewi (Fakultas MIPA Universitas Negeri Padang, 2018)
Science teaching in junior high schools should be conducted in integrated form. However, the real condition shows that in implementing integrated science teaching in the schools, there were several problems. The solution of this problem is to develop integrated science teaching materials by integrating real-world context and scientific literacy on Science teachers in East Agam district. The objective of the activity is to assist science teachers in developing integrated science teaching material and apply it in science teaching in the classroom. Participants of program assistance were 40 science teachers who were members of the Science MGMP in East Agam district. The instrument for collecting data consisted of pretest and posttest, performance assessment sheet, and questionnaire sheet of science teachers response. The data were analyzed by descriptive statistics analysis and correlated comparison test. Based on the results of data analysis can be stated that: 1). In implementing the program assistance, there are 32 products produced in integrated science worksheet form, 2). The average value of the science teacher's response to the implementation of program assistance for the development of integrated science teaching material can be classified into good category, and 3). The implementation of the program assistance for the development of integrated science teaching material is effective to improve the understanding of science teachers on the material of instructional material, the concept of integrated science learning, and the concept of scientific literacy.